2000
DOI: 10.1152/ajpheart.2000.279.5.h2431
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant pyruvate inhibits cardiac formation of reactive oxygen species through changes in redox state

Abstract: Myocardial ischemia-reperfusion is associated with bursts of reactive oxygen species (ROS) such as superoxide radicals (O(2)(-).). Membrane-associated NADH oxidase (NADHox) activity is a hypothetical source of O(2)(-)., implying the NADH concentration-to-NAD(+) concentration ratio ([NADH]/[NAD(+)]) as a determinant of ROS. To test this hypothesis, cardiac NADHox and ROS formation were measured as influenced by pyruvate or L-lactate. Pre- and postischemic Langendorff guinea pig hearts were perfused at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
82
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 26 publications
9
82
1
Order By: Relevance
“…The observation of NADH-induced ROS production in our study is consistent with others (27)(28)(29)(37)(38)(39). However, the mechanism is not well understood.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The observation of NADH-induced ROS production in our study is consistent with others (27)(28)(29)(37)(38)(39). However, the mechanism is not well understood.…”
Section: Discussionsupporting
confidence: 87%
“…It is also observed in patients with metabolic syndrome, diabetes, congestive heart failure, and various other diseases (34 -36). In a study of ischemia/reperfusion in the isolated guinea pig heart, Bassenge et al (37) showed that lactate stimulated ROS production severalfold, whereas pyruvate inhibited postischemic ROS production up to 80% in a dose-dependent way. The finding that lactate or cytosolic NADH induce an increase in ROS and inhibit I NCX may shed light on oxidative stress and abnormal Ca 2ϩ handling in the heart under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that dendritic cells presenting PK M1/M2 isozyme peptide can induce experimental allergic myositis in BALB/c mice (Kawachi et al, 2001). Tissue damage during myocardial ischemia/reperfusion can be reduced by the administration of pyruvate (Bassenge et al, 2000), and pyruvate, being a scavenger of hydrogen peroxide thereby reduces excessive production of free radicals, a process that has been implicated in the pathology of several neurodegenerative diseases including Parkinson's disease, Alzheimer's disease, and amyotrophic lateral sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which UCP-2 overexpression decreases NAD(P)H oxidase activity is presently unknown, but may be due to its effect on the cellular NADH/NAD + redox state. Bassenger et al reported that reduction of the NADH concentration : NAD + concentration ratio (NADH : NAD + redox) by pyruvate infusion dose-dependently inhibited NAD(P)H oxidase activity and ROS generation in perfused guinea pig hearts [30]. Therefore, it can be assumed that high-glucose-and Ang-II-induced mitochondrial membrane hyperpolarisation, which reflects impairment of mitochondrial electron transfer and respiration, would increase NAD(P)H oxidase activity by increasing the cytosolic NADH : NAD + ratio.…”
Section: Discussionmentioning
confidence: 99%